Altruism and Christian ethics - Grant, Colin, 1942- (New studies in Christian ethics., 2001)
"Separated from its anchorage in religion, ethics has followed the social sciences in seeing human beings as fundamentally characterized by self-interest, so that altruism is either naively idealistic or arrogantly self-sufficient. Colin Grant contends that, as a modern secular concept, altruism is a parody on the self-giving love of Christianity, so that its dismissal represents a social levelling that loses the depths that theology makes intelligible and religion makes possible."